Exploring on trees for landscape identity: a case study of Seri Iskandar Indian ethnic / Mohammad Arif Aiman Zulariffin and Helmi Hamzah - Zulariffin, Mohammad Arif Aiman; Hamzah, Helmi (2024)
The establishment of a distinct landscape identity is crucial in effectively representing a place, community, and culture, encapsulating their unique essence, and fostering a sense of belonging. The tree serves as the defining feature of the landscape, establishing its unique identity. However, there is a lack of understanding regarding the trees that represent the Indian ethnic group for landscape identity. This study explored the trees for landscape identity of Indian ethnic in Seri Iskandar, Perak, Malaysia. The study used a quantitative approach by analysing the tree preference data from the selected Indian community. The findings revealed that specific aspects such as native plants, water features, and architectural motifs rich in cultural symbolism were favoured for a Malaysian Indian garden. These insights hold significant value for policymakers and landscape professionals seeking to create gardens that embody the Malaysian Indian identity.